A New Approach to Astronomical Data Analysis Based on Multiple Variables - Prasenjit Banerjee; Asis Kumar Chattopadhyay; Soumita Modak (Advances in Astronomy)
Data analysis for a sample of celestial bodies generally is preceded by the completeness test in order to verify whether the sample objects are proper representatives of the corresponding part of the universe. A data set following a multivariate, continuous, uniform distribution is said to be “complete in space.” This paper introduces a new approach to check for this completeness for any astronomical data set under a multivariate setup. Our proposed procedure, using the multiple tests of hypotheses based on nonparametric statistics, and consequently, combining their p values, outperforms others from the literature.